2002
DOI: 10.1002/oca.704
|View full text |Cite
|
Sign up to set email alerts
|

Optimal control of innate immune response

Abstract: SUMMARYTreatment of a pathogenic disease process is interpreted as the optimal control of a dynamic system. Evolution of the disease is characterized by a non-linear, fourth-order ordinary differential equation that describes concentrations of pathogens, plasma cells, and antibodies, as well as a numerical indication of patient health. Without control, the dynamic model evidences sub-clinical or clinical decay, chronic stabilization, or unrestrained lethal growth of the pathogen, depending on the initial condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
101
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(103 citation statements)
references
References 28 publications
0
101
0
2
Order By: Relevance
“…Jung et al [17] applies optimal control theory to the treatments in a two-strain tuberculosis model. Stengel et al [18] demonstrated optimal control solutions to the innate immune response. Another control method, model-based predictive control, is also advantageous if accurate models are used in controller synthesis.…”
Section: A Control and Cell Biologymentioning
confidence: 99%
See 1 more Smart Citation
“…Jung et al [17] applies optimal control theory to the treatments in a two-strain tuberculosis model. Stengel et al [18] demonstrated optimal control solutions to the innate immune response. Another control method, model-based predictive control, is also advantageous if accurate models are used in controller synthesis.…”
Section: A Control and Cell Biologymentioning
confidence: 99%
“…Suppose that we have cells, and, for each cell, we introduce an output/observation map if the th cell is induced at time if the th cell is uninduced at time (18) where and are both fixed real numbers. Obviously, are random processes.…”
Section: A Control Architecturementioning
confidence: 99%
“…Commutatively, if we let 11 () r r t  and 22 () r r t  in equation (10) and its trajectory corresponding to the right-hand side of equation (11) such that we integrate using boundary conditions (12) and accounting for equations (14) and (15) with reversed time. Then the vector-valued functional of costate variables to be computed are:…”
Section: T T T T T V T V T P T P T M T T T T T Tmentioning
confidence: 99%
“…Application of quantum locally optimal algorithm of successive approximation as a concept of numerical methods, which accounted for the mathematical simulations of human immune systems problems using varying optimization control strategies for immune processes and HI-virus infections were adequately discussed in the models [2,[10][11][12][13][14][15]. Of particular interest to this present paper, is the mathematical formulation by [16], which was based on the findings of model [11].…”
Section: Introductionmentioning
confidence: 99%
“…Jung et al [10] apply optimal control theory to the treatments in a twostrain tuberculosis model. Stengel et al [11] demonstrated optimal control solutions to the innate immune response.…”
Section: Introductionmentioning
confidence: 99%